On an acute case of Chagas disease in a region under vector control in the state of São Paulo, Brazil - Wanderley, Dalva M.V.; Rodrigues, Vera L.C.C.; Leite, Ruth Moreira; Diaz, Sueli Yasumaro; Carvalho, Maria Esther; Santos, Soraya O.; Tatto, Érica; Carli, Maria Salete; Coelho, Kunie I.R.; Silva, Paulo Ribeiro da; et al. (BEPA. Boletim Epidemiológico Paulista, 2014)
No vector transmitted cases of Chagas disease had been notified in the state of São Paulo since the 1970s. However, in March, 2006, the death of a sixyear- old boy from the municipality of Itaporanga was notified to the Center for Epidemiological Survey of the São Paulo State Health Secretariat: an autochthonous case of acute Chagas disease. The postmortem histopathological examination performed in the Hospital das Clínicas of the Botucatu School of Medicine confirmed the diagnosis. Reference to hospital records, consultation with the health professionals involved in the case and interviews with members of the patient’s family supplied the basis for this study. We investigated parasite route of transmission, probable local reservoirs and vectors. No further human cases of acute Chagas disease were diagnosed. No locally captured vectors or reservoirs were found infected with Trypanosoma cruzi. Alternative transmission hypotheses - such as the possible ingestion of foods contaminated with vector excreta - are discussed, as well as the need to keep previously endemic regions and infested houses under close surveillance. Clinicians should give due attention to such signs as uni- or bilateral palpebral edema, cardiac failure, myocarditis, pericarditis, anasarca and atypical signs of nephrotic syndrome or nephritis and consider the diagnostic hypothesis of Chagas disease.